2017
DOI: 10.1007/s10639-017-9615-0
|View full text |Cite
|
Sign up to set email alerts
|

“It must not disturb, it’s as simple as that”: Students’ voices on mobile phones in the infrastructure for learning in Swedish upper secondary school

Abstract: Drawing from a survey and focus group interviews, this study explores how Swedish upper secondary students reason about the usage of their personal mobile phones in school. As a contribution to the debate around the mobile phone's role in school, we present the students' own voices relative to the question of regulating mobile phone use. We use the notion of infrastructure for learning (Guribye and Lindström 2009) to analytically approach the social and technological dimensions of the students' narratives on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 31 publications
(43 reference statements)
4
59
0
1
Order By: Relevance
“…It has been found that teachers and students have different ideas about how mobile phones could be used supportively but are also problematic in school activities (Ariel and Elishar-Malka 2019). Although students use mobile phones for their schoolwork, teachers can regard this as a distraction (Ott et al 2018). Additionally, many teachers are worried that students' mobile phone use could cause problems.…”
Section: Different Ideas Of Mobile Phone Usementioning
confidence: 99%
See 3 more Smart Citations
“…It has been found that teachers and students have different ideas about how mobile phones could be used supportively but are also problematic in school activities (Ariel and Elishar-Malka 2019). Although students use mobile phones for their schoolwork, teachers can regard this as a distraction (Ott et al 2018). Additionally, many teachers are worried that students' mobile phone use could cause problems.…”
Section: Different Ideas Of Mobile Phone Usementioning
confidence: 99%
“…Thus, some teachers advocate strict regulation, and teacher-driven use (Dinsmore 2019). In contrast, a teacher-centered division of labor and its rules against mobile phone use risk leading to significant opposition from students (Dinsmore 2019;Fernandez 2018;Gentina et al 2018;Ott et al 2018). This is because students might consider that mobile phones are useful for their schoolwork (Fernandez 2018;Ott et al 2018).…”
Section: Different Ideas Of Mobile Phone Usementioning
confidence: 99%
See 2 more Smart Citations
“…For instance, research on teachers has focused on their use of or opinions about ICT Ryan et al 2010) and their competencies and strategies to enact ICT in teaching (Keane and Keane 2017). Among other things, research on students has focused on their use and views of ICT in general (Olofsson et al 2018;Bulfin et al 2016) and of specific digital hardware, software or applications in particular (Duran and Aytaç 2016;Ott et al 2018;Towndrow and Fareed 2015;Räihä et al 2014). An increased research focus can also be seen on students' views of the 1-1 concept (Keane and Keane 2017;Spanos and Sofos 2015), mobile use (Gromik 2017), coding (An 2016;Falloon 2016) and the idea of a 'flipped classroom' (Hatakka et al 2013;Limniou et al 2018).…”
Section: Introductionmentioning
confidence: 99%